Kobiety na politechnikach - trajektorie codzienności w kontekście współczesnych przemian społeczno-ekonomicznych - Szymczak, Emilia (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
A variety of socio-economic transformations which we are witnessing, and which accompany us during our existence are a contribution to a number of other phenomena, which are a kind of repercussion, often leading up to significant cultural changes. Sometimes we can recognize them, by the denial of the eternal divisions, order and structure, as a kind of cultural revolution. One of the visible changes in the field of today’s higher education that I would like to address in this article is a growing participation of women in technical universities. This phenomenon seems to be a kind of confirmation of successive bridging of borders and dichotomies in the field of traditionally understood social and gender roles. The purpose of this article is to present these changes and to identify the factors that determine them socio-economically.
Keywords: ekonomia; kobiety; kultura; politechnika; socjologia; szkolnictwo wyższe